AUDIT ENERGI PROSES PENGOLAHAN TEH HITAM (CTC) DENGAN SISTEM PENGAMBILAN KEPUTUSAN METODE SPACE - Muhammad Rizky Ramanda; Sarifah Nurjanah; Asri Widyasanti (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2021)
The favorite product of black tea is tea leaf that are ground using the crush, tear and curl (CTC) method. This process able to produce the dry tea which has high quality with a strong aroma and taste, and high levels of antioxidants. This study aimed to conduct an energy analysis on the processing of black tea CTC at PTP. Nusantara VIII Rancabali to find out the steps towards efficient use of energy, opportunities and conservation efforts. The research method used is descriptive analysis method. The present paper conducted the energy audit calculations which are based on the energy consumption in each tea processing activity from the time. The calculation of energy audit was conducted from preparation of raw materials until the packaging of tea product. The results of the energy audit on the CTC black tea processing showed that for each ton of tea leaves required the energy is about 3.930,66 MJ.ton-1The greatest energy use is drying process which is at 1.424,67 MJ.ton-1 or 36,24%. The results of the analysis space was at quadrant conservative aggressive. Aggressive conservative steps that can be taken in the black tea processing are to develop activities towards energy saving, such as changing fuel from ordinary wood to wood pellets and adding or modifying machine tools so that the installed capacity of each processs to fulfill the capacity input of leaf tea. Key words: CTC, energy analysis, energy saving, processing of tea